2021
DOI: 10.5144/0256-4947.2021.121
|View full text |Cite
|
Sign up to set email alerts
|

Myometrial myxoidosis in a patient with systemic lupus erythematosus

Abstract: Myometrium myxoidosis is new terminology to describe a non-neo-plastic process of extracellular mucinous accumulation in the myometrium wall of the uterus. We report a rare association of myometrial myxoidosis with lupus erythematosus in a 35-year old woman with a history of leiomyoma. At presentation, this case was diagnosed as a pelvic abscess and treated with specific antibiotherapy, and then discharged after clinical improvement. One week later, after recurrence of the symptoms, the patient underwent hyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Three cases of myometrial myxoidosis associated with SLE have been reported. 7,8 The mucin material is positive for Alcian blue staining at pH 2.5 and sensitive to hyaluronidase digestion, while mucicarmine staining is weakly positive. 7 The findings are suggestive of hyaluronic acid accumulation, the same result as cutaneous mucinosis.…”
Section: Discussionmentioning
confidence: 99%
“…Three cases of myometrial myxoidosis associated with SLE have been reported. 7,8 The mucin material is positive for Alcian blue staining at pH 2.5 and sensitive to hyaluronidase digestion, while mucicarmine staining is weakly positive. 7 The findings are suggestive of hyaluronic acid accumulation, the same result as cutaneous mucinosis.…”
Section: Discussionmentioning
confidence: 99%